PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT, KEPERCAYAAN DAN PEMBERIAN HADIAH TERHADAP KEPUASAN PELANGGAN MADU GIZIDAT PT ETHOS KREATIF INDONESIA - Werdiasih, Rustina Dewi (JURNAL EKONOMI, 2022)
The purpose of this study was to analyze the influence of customer relationship management, trust and gift giving on customer satisfaction Madu Gizidat PT. Indonesian Creative Ethos. This study uses quantitative methods. The data used for hypothesis testing is primary data obtained from distributing questionnaires to customers of Gizidat Honey with a total sample of 100. The sampling technique used was purposive sampling method. Data testing techniques in this study include validity test with reliability test, classical assumption test, multiple linear analysis, partial test and simultaneous test as well as the coefficient of determination test (R2). Analysis of the data in this study using the help of statistical software. Based on the results of multiple linear analysis research, it is known that the customer relationship management variable, trust, gift-giving, has a positive and significant influence on customer satisfaction with a constant value of 3.849 with a positive regression coefficient value of the customer relationship management variable (0.240),confidence (0.354), gift-giving(0.311). While the results of the partial test are known that the customer relationship management variable has a positive and significant effect on satisfaction with the results of the value ofT count is greater than T table of (2,059 > 1,985) with a significance (0,042 < 0,05). Trust variablehas a positive and significant effect on customer satisfaction with the results ofT count is greater than T table of (4.512 > 1.985) with a significance (0.000 less than 0.05). Gift giving variablehas a significant influence on customer satisfaction with the results of the value ofT count is greater than T table of (3.121 > 1.985) with a significance (0.002 < 0.05). And the results of the simultaneous test show that customer relationship management, trust, gift-giving, has positive and significant influence on customer satisfaction with a calculated F value of 25,653 withF table of 2.70 so that F arithmetic > F table (25.653 > 2.70) with a significance (0.000 less than 0.05).